Terrorism or the never ending story (Reflections on a round table) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Terrorism is a human activity that poses three grave problems: a) It is one of the gravest and bloodiest crimes as far as results are concerned and nonetheless, it is the one in which the perpetrators are least burdened by guilt. b) It is a pretext for political manoeuvres on the part of the Governments affected, who use terrorism as electoralbait. c) In both cases, terrorists or politicians use incredible language, in which the most elementary rules of grammar or logic are transformed into mere meaning less sounds in which either side maintains a stance from which neither will backdown. There are numerous situations that show that terrorists are the world’s worst criminals with the clearest conscience. Firstly, the widespread belief among professors that Law and Morality are two separate worlds makes not only the authors of terrorist acts but also its critics scoff at the accusation of terrorists’ behaviour as gravely immoralas long as it is not also qualified as dysfunctional. The difficulty or impossibility of dogmatically defining terrorism causes its perpetrators to remain unfazed by something that cannot be defined. And the idea that terrorism is a political crime encourages terrorists’ legal counsels to try to prove –in spite of what has been established in Constitutions and International Treaties– that terrorists deserve preferential treatment when precisely the contrary should be true: that today the commission of a political crime is much more serious than the commission of a common crime. The ruling class, on its part, insists on making terrorism a political issue, conver sing with terrorists to demonstrate its democratic disposition and downplaying terrorists’crimes (as if the decision to prosecute them were up to the Government’s discretion), trying to demonstrate to outsiders that peace is just around the corner, and to insiders that they hope to obtain more votes in the next elections (in spite of the dysfunctional image conveyed of the victims of terrorism demanding justice). Moreover,since everything is negotiable and the most valuable objective is peace, what is important is ensuring that peace and “letting the dead bury the dead”. The worstpart of it is that it is all a lie: Morality does not cease to have anything to do with the Law, nor does a political crime deserve preferential treatment, nor are terrorists evergoing to lay down their arms, nor is everything negotiable at any moment, nor ispeace the most valuable commodity (freedom is), nor... I have provided some examples of the caricature-like language with which bothgroups pull our leg, but there are even more. Terrorists say they are not guilty of the crimes they commit, because these acts are the Government’s fault for not granting them the independence they demand. The ruling class claims that the ones to blame for the alarm that terrorism produces is not the Government, who deals with terrorists as equals, but the members of the opposition party, who denounce what is happening.The messenger is the one to blame. A man of good faith is one who for goes the rights (of others) to transmit an image of good faith, just as a politician of good faith is one who buys votes (with other people’s money) and continues to think that ETA is going to cease its violence if it is addressed in the terms it wants to hear, ignoring the fact that using its terms implies recognising it as a legitimate armed forceand not as organised crime or a contemptible band of criminals that only know how to kill with explosives or a shot in the back, taking care not to destroy them selves in the process. Let Belgium keep protecting them, now that the European Union’s initiative has withered on the vine.
Keywords: Guilty conscience; organised crime; political crime; Law and Morality; Politics; legal language; political language; negotiation; peace (as a fundamental right); terrorism